Use of Kamar® heatmount detectors in beef cattle synchronized with Lutalyse® - G.H. Kiracofe; M. Heekin; Kenneth G. Odde; M. King (Kansas Agricultural Experiment Station Research Reports, 1981)
The ability of the Kamar Heatmount Detector to identify cows ready for insemination 80 hours after two Lutalyse injections was tested with 439 beef cows and heifers. The detector was placed on the rump at the second injection and was "read" at insemination. Conception rate from the 80-hour timed insemination for cows with red (activated) and lost detectors was 56.5% compared with 7.6% of the cows with white detectors.
Keywords: Cattlemen& #x27; s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Kamar detector; Lutalyse